Изоморфизм групп продольных и поперечных колебаний винтового стержня - Ванин, В. А.; Григорьев, А. А. (НТУ "ХПИ", 2010)
Проаналізовано прикладні та гносеологічні аспекти симетрії рівнянь, що моделюють повздовжні і поперечні коливання гвинтового стрижня. Досліджені форми гармонічних коливань, що використовуються при синтезі гвинтових хвиль трансляції. Показано, що у хвиль середнього частотного діапазону відношення кручення і кривизни пропорційно частоті, і це є передумовою їх квантування. Сформульовані обмеження амплітуд коливань виходячи із умов міцності стрижня.

The applied and the gynecological aspect of the symmetry of the equitation are modeling the longitudinal and the cross – section oscillations of the screw rod are analyzed. The forms of the harmonic oscillations used by the synthesis of the spiral repeater waves are examined. It is shown that the waves of the middle frequency range have an equal degree of the torsion and the curvature towards the frequency and that is the basis of their quantization. The restrictions of the oscillations amplitude caused by the conditions of the rod’s strength are defined.
Keywords: фононы; винтовые волны трансляции; информационное поле; колебания